Significant Increase in Blood Pressure Following BNT162b2 mRNA COVID-19 Vaccination among Healthcare Workers: A Rare Event - Nikolaos Syrigos; Anastasios Kollias; Dimitra Grapsa; Eleni Fyta; Konstantinos G. Kyriakoulis; Ioannis Vathiotis; Elias Kotteas; Ekaterini Syrigou (Vaccines, 2022)
This brief report examined the frequency and characteristics of a significant blood-pressure (BP) increase after Pfizer-BioNTech BNT162b2 vaccination among healthcare workers who were advised to measure their BP at home. A total of 797 participants (mean age 48.1 ± 10.8 years, 63% women, 39% smokers) were included in the analysis. Seven participants reported an increase in their BP (three in the range of grade 2 and four in the range of grade 3 hypertension). Only one participant had a history of treated hypertension. The BP increase was observed at the end of the first week after the first dose, lasted for 3 to 4 days, and recurred promptly after the second dose. Only one case required hospitalization, mainly due to a history of cardiovascular disease (follow-up). Individuals experiencing a BP increase compared with those not reporting issues with their BP had a higher mean age and similar distribution of sex and non-smoking status. In conclusion, a significant BP increase after Pfizer-BioNTech vaccination seems to be rare and of a benign and transient nature. Monitoring the BP before and after vaccination might be advisable only for selected individuals with a high cardiovascular risk.